Word Formation in Arabic: A Morphological Analysis of Egyptian-Produced Snacks - Fitriyah, Tika; Amrulloh, Muhammad Afif; Nashoih, Afif Kholisun (Institut Agama Islam Negeri (IAIN) Metro, 2023)
Like any other language, Arabic continues to evolve in line with the times. This can be seen with the emergence of new vocabulary. Studying word formation in Arabic is essential to trace the development of Arabic used by people in this era. This study analyzes Arabic word formation in snack products produced in Egypt. This research is qualitative research with a descriptive method. The research data was taken from several shops in Cairo, Egypt, and as many as 20 products in September. The data were collected using observation and documentation methods. One hundred ninety-seven data were selected using a simple random sampling technique. The data were analyzed using content analysis with a morphological approach regarding word formation. This study found various forms of words with the formation process of derivation, affixation, and borrowing. Based on these findings, the formation of Arabic words in snack food products in Egypt continues to develop, so this study can contribute to fulfilling the need for new word formation in Arabic.